Manufacture and general cost analysis of o natural Biopolymerfrom the calyx of Physalis peruviana 1 (uvilla) - Sarango Ortega, Yessenia; Sónchez Juórez, A.; Capa Benítez, Lenny Beatriz (Revista Universidad de Guayaquil, 2016)
Biopolymers are macromolecules present and synthesized by living beings, to which they can perform chemical transformations in order to obtain products and are considered as biodegradable material. They are classified according to their source of origin inthree subgroups: elaborated from biomass, with bioderivative monomers and those that are synthesized by microorganisms. We can find them in agricultural crops, pastures, vegetable oils or forest or organic residues such as calyx of Physalis peruviana L. This biopolymer could be used in society as a singular industrialization in a sustainable aspect within agriculture; and whose properties favor sustainable economic development and sustenance to the productive matrix. By using them you can reduce the manufacture of polymers that are made with recalcitrant oils or stone material that accumulate in the environment causing pollution. Therefore, in this research we have set ourselves the following objective: to elaborate a protocol for the manufacture of a biopolymer based on calyx of Physalis peruviana L. The preparation of the biopolymer took in three phases: pulpaje treatment, bleaching treatment and elaboration of the biopolymer and the transparency was evaluated by optical spectroscopy and solubility by massloss. The biopolymer was obtained with the protocol based on acetic acid and glycerin and was obtained a 28% transparency. Finally realized a general cost analysis was performed on the manufacture of a cellulose biopolymer made from uvilla calyx with favorable properties.
Keywords: starch; polymer; cellulose; Physalis peruviana